Analysis of the Technology Acceptance Model (TAM) in the implementation of the curriculum review course: a study on students’ understanding and acceptance of technology at Universitas Islam Sumatera Utara - Evi Susilawati; Susi Ekalestari; Chairina; Imamul Khaira; Harahap, Evi Syuriani; Sapta Kesuma; Nana Mardiana (Penerbit UiTM (UiTM Press), 2025)
This study analyses the implementation of the Technology Acceptance Model (TAM) in the Curriculum Review course among students of Universitas Islam Sumatera Utara. This study aims to identify the factors that influence students’ acceptance and understanding of technology in the learning process. A quantitative approach was employed, utilising a structured survey distributed to 125 selected participants using the purposive sampling technique. The research instrument is a questionnaire developed based on TAM constructs, including (1) perceived usefulness, (2) perceived ease of use, and (3) attitude toward using. Data analysis employs Structural Equation Modelling (SEM) techniques to examine the relationships between variables. The research hypothesis examines the impact of perceived usefulness and perceived ease of use on attitudes and intentions to utilise technology in learning. The results show that: (1) perceived usefulness of technology among students positively affects attitudes toward using technology (β=0.65, p<0.05), (2) perceived ease of use of technology among students significantly positively affects attitudes toward using technology among students (β=0.58, p<0.05), (3) attitudes towards using technology among students significantly positively affect intentions to use technology among students (β=0.72, p<0.05). The TAM model is proven to explain 68% of the variance in technology acceptance among students. This suggests that the understanding and acceptance of technology among students in the Curriculum Review course are influenced by the perceived usefulness and ease of use, which are in turn mediated by attitudes toward using technology.